Evaluating Different Methods to Establish Biodiverse Swards of Native Grasses and Wildflowers for Pasturelands - Jonathan O. C. Kubesch; Scott P. Greiner; Gabriel J. Pent; J. Leighton Reid; Benjamin F. Tracy (Agronomy, 2024)
Many cool-season pastures in the southeastern U.S. are dominated by a competitive cool-season grass, tall fescue (Schedonorus arundinaceus), and lack substantial plant diversity. Planting native warm-season grasses (NWSGs) and wildflowers (WFs) into these pastures could provide summer forage for cattle and more floral resources for pollinators. This paper summarizes field experiments designed to evaluate different spatiotemporal planting arrangements of NWSGs and WFs to improve their establishment success. The study was conducted from April 2021 to October 2023 in central Virginia (USA). Planting treatments included NWSG and WF mixtures planted: (1) together in the same space, (2) spatially separated in space (i.e., side by side), or (3) temporally separated where NWSGs and WFs were planted in difference sequences. Results showed few differences in forage mass, floral production, and botanical composition as well as stand density in 2021 and 2022. In 2023, NWSG abundance was greater where grasses were planted first or mixed with WFs. Similarly, the WF component was favored when they were planted before NWSGs. Overall, planting NWSG and WF mixes separately, either spatially or temporally, favors successful establishment and could offer more flexibility for using selective herbicides to suppress the heavy weed pressure that often accompanies these plantings.